Abundance of Mepraia spinolai in a Periurban Zone of Chile - Pedro E Cattan; Angélica Pinochet; Carezza Botto-Mahan; Mariana I Acuña; Mauricio Canals (Memorias do Instituto Oswaldo Cruz, 2002)
Mepraia spinolai is a silvatic species of Triatominae which prefers microhabitats near to or in rock piles. It is also able to maintain similar or higher size populations near houses. The density of bugs in quarries near Santiago, Chile, differed within microhabitats and varied significantly within sites according to season. M. spinolai was not found in sites characterized by human perturbation of quarries. Our results confirm M. spinolai as a silvatic triatomine whose importance as a vector of Chagas disease will depend on contact with humans. This could occur if the habitats where populations of this species are found become exploited for the building of urban areas.